2016
DOI: 10.1080/01459740.2016.1255610
|View full text |Cite
|
Sign up to set email alerts
|

Assisted Suicide as a Remedy for Suffering? The End-of-Life Preferences of British “Suicide Tourists”

Abstract: The highly charged debate about the moral status of assisted suicide features regularly in the news media in medically advanced countries. In the United Kingdom, the debate has been dominated in recent years by a new mode of death: assisted suicide in Switzerland, so-called suicide tourism. Drawing on in-depth interviews with people who were actively planning on 'going to Switzerland,' alongside participant-observation at a do-it-yourself self-deliverance workshop, I discuss how participants arrived at their d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 27 publications
(22 reference statements)
1
23
1
5
Order By: Relevance
“…Medicine's power to frame and manage aspects of human existence moves into clear focus here. The participation of medical professionals in aided deaths not only affords patients a key measure of social legitimacy, but it also diffuses attendant moral responsibilities for their death and increases chances for a successful outcome because of the perceived technical know‐how of clinicians (see Richards 2017, 353). According to one prescribing physician in Portland, once he began offering his attendance at their deaths, nearly all his patients have taken him up on it, even though all he does is watch the patient drink the lethal medication.…”
Section: The Medicalization Of Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…Medicine's power to frame and manage aspects of human existence moves into clear focus here. The participation of medical professionals in aided deaths not only affords patients a key measure of social legitimacy, but it also diffuses attendant moral responsibilities for their death and increases chances for a successful outcome because of the perceived technical know‐how of clinicians (see Richards 2017, 353). According to one prescribing physician in Portland, once he began offering his attendance at their deaths, nearly all his patients have taken him up on it, even though all he does is watch the patient drink the lethal medication.…”
Section: The Medicalization Of Deathmentioning
confidence: 99%
“…The state-through its medical professionals-thus preserves the right to determine who gets to opt out of life and to differentiate between a moral and an immoral death. It is precisely the involvement of physicians and state authorities that lends medically assisted deaths a significant measure of social and moral legitimacy-a quality notably absent in popular understandings of suicide and in cases where terminally ill people use "do-it-yourself " methods to end their own lives (Richards 2017).…”
Section: Authorizing Death and The Limits Of Autonomymentioning
confidence: 99%
“…As research undertaken by one of the authors has shown, even among Christians, belief in the redemptive potential of suffering is no longer a given, and Christians as well as those of other faiths, also opt for assisted dying. [46] The option to lawfully end your life with assistance validates the view that there is no value in dying unless the suffering person says so. We therefore contend that lawful assisted dying will further champion an evolving cultural script that constructs any form of pain and suffering at the end of life as meaningless and untenable, as well as fundamentally questioning the belief that suffering at the end of life yields particular forms of compassion and relations between people.…”
Section: The Suffering Experiencementioning
confidence: 90%
“…(Eutanasi er derimot forbudt i straffeloven.) Sveits har lenge hatt en «selvmordsturisme»: Pasienter fra andre land drar dit for å begå selvmord med medikamenter (Richards, 2016), også norske pasienter (Materstvedt, 2015b).…”
Section: Av-medikalisering Av Selvmord?unclassified
“…Lov om eutanasi og assistert selvmord. (2016). www.parl.gc.ca/ HousePublications/Publication.aspx?DocId=8384014 Cook, M. (2016.…”
Section: Avsluttende Merknadermentioning
confidence: 99%